Application of ozone therapy in intervertebral disc protrusion: clinical case (Ozone Therapy Global Journal, 2020)
Intervertebral disc disease also known as "Extrusion of the nucleus pulposus of not degenerated discs," is a condition that triggers pain, disability or total paralysis and affects dogs and cats. The objective of this work was to demonstrate the effectiveness of ozone therapy in the treatment of a canino patient with disc protrusion. Presented to query a female of breed poodle / Maltese two-year-old with a history of trauma, it was diagnosed by magnetic resonance imaging the presence of discal protrusions in the intervertebral spaces L1-L2 and L2-L3 with involvement of nerve roots L1 and L2 bilateral. Ozone therapy treatment consisted of 20 sessions under the following order: daily (30 mL to 25µg/mL concentration) rectal Insufflations, paravertebral two times a week with five days difference between one and another application to L2 and L3 (4 bilateral mL to) concentration of 15µg/mL), also was sent to rehabilitation the patient. The result of the treatment showed the total recovery of the patient who avoided surgery, monitoring daily the patient (unfortunately was not possible to perform another MRI for the high cost). In conclusion, the paravertebral ozone therapy in disc protrusion proves to be effective, safe and problem-solving in these cases.